Relationship between Metabolic Syndrome and Depression in elderlies with Cardiovascular Disease - V Shojaeimotlagh; N Lazari; M Ghalenoee; S Saleh Abadi; N Parizad; R Ghanei Gheshlagh (Iran University of Medical Sciences, 2015)
Abstract   Background & Aim: Metabolic syndrome is one of the risk factors of cardiovascular disease. Depression increases the risk of metabolic syndrome in the general population. The aim of this study was determining the association between depression and the metabolic syndrome in elderlies with cardiovascular disease.   Material & Methods: This cross-sectional study was conducted on 200 elderlies with cardiovascular disease hospitalized in Saqqez's Imam Khomeini's hospital in 2013 with convenience sampling. To evaluate depression, Geriatric Depression Scale (GDS) and to assess metabolic syndrome, ATP3 index were used. Data was analyzed by descriptive statistics, independent T test and Chi square using PASW. The significant level for all the tests was 0.05.   Results: The results showed that 61 percent of the patients have experienced the symptoms of depression and 46 percent of them had metabolic syndrome. The chance for metabolic syndrome in women was 2/4 times more than men (95% CI:1/3-4/2, OR=2/4, p=0/003). There was no significant relationship between metabolic syndrome and depression (p=0/198). Among the components of metabolic syndrome only systolic blood pressure was associated with depression (P=0/002), so that the chance for high systolic blood pressure in depressed elderlies was 2.5 time more than those without depression (95% CI: 1/4-4/5, OR=2/5, P=0/003).   Conclusion: Given the high frequency of depression and metabolic syndrome in elderlies with cardiovascular disease, more attention should be paid on the simultaneous occurrence of these two problems.